Why is the histomorphological diagnosis of tumours of minor salivary glands much more difficult? - Ihrler, Stephan; Agaimy, Abbas; Guntinas-Lichius, Orlando; Haas, Christian J.; Mollenhauer, Martin; Sandison, Ann; Greber, Lukas (Histopathology, 2021)
Aims: There is a widespread perception among clinicians and pathologists that the histomorphological assessment of minor salivary gland (MinSG) tumours is more difficult and hampered by more misdiagnoses than that of major salivary gland tumours. This is based on a vague, subjective clinical impression, lacking scientific proof. The aim of the present study was to identify and statistically verify potential reasons that could explain this difference. Methods and results: We identified 14 putative clinical, pathological and combined clinicopathological reasons that, altogether, could explain the phenomenon of the perceived greater diagnostic difficulty associated with MinSG tumours. We performed a comprehensive literature search and a statistical comparison of data from a large personal consultation series (biased for difficult cases) with cumulated data from straightforward, unselected (non-consultation) series from the literature. By performing this comparison, we identified, with statistical significance, a comprehensive series of reasons, as well as of consequences, of the greater difficulty in diagnosing MinSG tumours. Conclusions: Among the 14 criteria, high frequencies of initial incisional biopsies and of a low-grade category in malignant tumours emerged as the two most important reasons for enhanced diagnostic difficulty. Very rare entities, unusual locations, shortcomings in clinicopathological communication, and pecularities of the special anatomical location of the hard palate, such as tumour necrosis, mucosal ulceration, pseudoinvasion, and the peculiar phenomenon of ‘tumoral–mucosal fusion’, contribute to further diagnostic difficulties. The awareness of these shortcomings and pitfalls enables us to provide a series of recommendations for clinicians and pathologists that might aid in assessment and reduce the rate of misdiagnosis of MinSG tumours.
CRIS-Team Scopus Importer:2021-08-27
Keywords: consultation cases; minor salivary glands; molecular testing; palate; pitfall; salivary carcinoma; second opinion